Central Nervous System Opportunistic Infections - Agnihotri, Shruti P. (Seminars in Neurology, 2019)
Opportunistic infections of the central nervous system are classically associated with immunosuppression arising from infection with human immunodeficiency virus and with various hematologic malignancies. However, over the past few years, they are increasingly associated with transplantation and various immunosuppressive treatments used to treat autoimmune diseases. They cause significant morbidity and mortality and remain a diagnostic challenge due to the absence of typical signs and symptoms of infection and mimicry by various noninfectious causes. The pathogens associated with these infections are often commonly found pathogens of low virulence in immunocompetent hosts and include various bacteria, parasites, fungi, or viruses. These infections can present as various clinical syndromes, including meningitis, encephalitis, space-occupying lesions, stroke-like presentations, or even neoplastic manifestations. Progressive multifocal leukoencephalopathy can be seen in patients with multiple sclerosis on various new immunomodulatory drugs in addition to patients with human immunodeficiency virus, transplantation, or hematologic malignancies, and is characterized by multifocal white matter lesions. Human herpesvirus-6 causes severe encephalitis in transplant recipients, known as posttransplantation acute limbic encephalitis. Neoplastic manifestations like Epstein–Barr virus-associated primary central nervous system lymphoma and posttransplantation lymphoproliferative disorders are particularly challenging to diagnose and manage. Modern diagnostic techniques, including advanced imaging techniques like magnetic resonance spectroscopy, use of polymerase chain reaction, and metagenomic sequencing, can be helpful in early recognition of pathogens. Treatment of most of these involves lowering of immunosuppression when possible and use of specific antimicrobial agents when available. Improved outcomes can be seen when early diagnosis is made.
Keywords: CNS opportunistic infections; posttransplant; progressive multifocal leukoencephalopathy; EBV